Enables Indonesia scanning the challenges of fisheries development in a time of pandemic - LL.M, Rachma Indriyani; Abdul Rahim, Asmar; Azmi, Ruzita (2020)
The COVID-19 crisis has created the novel law enforcement challenges that different approach must take in order to address risk of non-compliance. Amidst the pandemic, these days monitoring and enforcement will be fully depended on how each State enables to overcome law-breaking activities against sustainable fishing. It argues that while Indonesia government has ordered to sustain productivity and fish harvesting in a time of pandemic, some off-shore fisheries with targeting highly migratory fish such as tuna catch, look like they are going very strong. Large fishing boats that can process and freeze fish are staying out at sea. The outcome reveals that while the cops are watching closely national marine territory, however, examination of law enforcement in high seas fishing, as for Indonesia interest, is not that pronounced. Indonesia need to consider some modified enforcement against those non-compliances by conducting investigation in the particular fishing area to scan possible non-compliance acts that shall take place.